Physiochemical characterization of Sn-Zn coatings electrodeposited from an acidic chloride bath in the absence of complexing agent - Nor Hairin, Assayidatul Laila; Othman, Raihan; Rizal, Faireez; Mohd Daud, Farah Diana (UR Publishers, 2017)
The purpose of this study is to identify theZn2+ions concentrationat Sn-Zn coating which could be produced in the absence of a complexing agent. The electrolytic bath comprised of SnCl2 and ZnCl2. The ionic mole ratio Zn2+/Sn2+ of the electrolytic bath studied were 1:2, 1:1, 2:1, 4:1 and 10:1. Pure Zn and Sn electrodeposits were also prepared. The deposition process was performed at constant current of 5 mA and deposition time of 120 min. The electrodeposits were analyzed using X-ray diffraction (XRD) and scanning electron microscopy (SEM). It was found that in the absence of complexing agent, even an electrolytic bath with Zn2+/Sn2+ ionic ratio of ten folds could not produce Zn-rich of Sn-Zn electrodeposits. Further, a unique method has been introduced to characterize the electrodeposits i.e. using the metal-air electrochemical cell. In this method, the electrodeposits were coupled with an air electrode in an alkaline electrolyte (6 M KOH) and discharged at 1 mA. Specific metallic element content will produce a distinct discharge profile thus enables it to be used in characterizing alloys or composites.